A dosimetric comparison of linac-based stereotactic fractionated radiotherapy techniques for pituitary adenoma and craniopharyngioma. Issue 3 (20th February 2018) - Varghese, Sunitha S.; Goudar, Giriyappa; Abraham, Susen; Peace, Timothy; Singh, Rabi R.; Backianathan, Sevamani
Abstract: Aim: To compare the dosimetric outcomes of linear accelerator-based stereotactic radiotherapy (SRT) techniques—static conformal field (SCF), static conformal arc (SCA) and dynamic conformal arc (DCA), for treating pituitary adenoma and craniopharyngioma. Materials and methods: Computer image sets of 20 patients with pituitary adenoma or craniopharyngioma and treated with post-operative SRT were selected for this study. For each dataset, three SRT plans, with SCF, SCA and DCA techniques were generated using Brain LAB, iPlan RT V.4.5.3, TPS software. The conformity index (CI), homogeneity index (HI), quality of coverage of the target, dose–volume histograms for the target and organs at risk (OARs) and the time taken to deliver treatment was compared across three sets of plan. Results: There were 12 patients with pituitary adenoma and eight with craniopharyngioma. The CI and HI were comparable across three techniques. The quality of coverage was superior in DCA technique. OARs were better spared in SCF and DCA techniques. Time taken to deliver treatment was least in SCF technique. Conclusions: The linac-based SRT techniques SCF, SCA and DCA are efficient in delivering highly conformal and homogenous dose to the target in pituitary adenoma and craniopharyngioma. Among these three techniques, SCF and DCA had acceptable quality of coverage. The dose received by OARs was least in the SCF technique.